Post-Vaccination Monitoring of Foot and Mouth Disease (FMD) in Morowali Regency, Central Sulawesi - Yuliani Suparmin; Nevyani Asikin; Fitriani; Zainal; Vilzah Fatimah (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2026)
One of the main strategies for controlling Foot and Mouth Disease (FMD) in Indonesia is the implementation of a livestock vaccination program. Post-vaccination monitoring is essential to evaluate vaccine effectiveness and the overall success of the vaccination program as a basis for future FMD control policies. The evaluation of FMD vaccination outcomes in this study was conducted using the Enzyme-Linked Immunosorbent Assay (ELISA) technique. ELISA was applied to detect antibodies against the FMD virus in post-vaccination livestock serum samples. The Non-Structural Protein (NSP) ELISA method was used to screen for antibodies indicative of exposure to the field FMD virus, as NSP antibodies are generally produced only following natural infection and are not induced by vaccination. The NSP-ELISA results from 24 serum samples showed that 16.67% (4 samples) were seropositive, while 83.33% (20 samples) were seronegative. NSP seropositivity indicates exposure to the field FMD virus, whereas the high proportion of seronegative animals suggests that most vaccinated livestock were not exposed to the virus under field conditions. These findings demonstrate that the FMD vaccination program in Morowali Regency, Central Sulawesi, plays an important role in preventing virus transmission and reducing field infection rates in livestock.